1998
DOI: 10.1172/jci1528
|View full text |Cite
|
Sign up to set email alerts
|

Decreased dependence of myelin basic protein-reactive T cells on CD28-mediated costimulation in multiple sclerosis patients. A marker of activated/memory T cells.

Abstract: Although multiple sclerosis (MS) patients and healthy individuals have similar frequencies of myelin basic protein (MBP)-specific T cells, the activation state of these cells has not been well characterized. Therefore, we investigated the dependence of MBP-reactive T cells on CD28-mediated costimulation in MS patients, healthy controls, and stroke patients. MBP-reactive T cells from healthy controls and stroke patients failed to proliferate efficiently when costimulation was blocked using anti-CD28, consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
1
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(145 citation statements)
references
References 33 publications
7
134
1
3
Order By: Relevance
“…In contrast, myelin-reactive T cells from the PB of healthy controls are Kv1.3 low , consistent with a naive͞T CM phenotype (11). Our results corroborate reports by other investigators who have found a preponderance of chronically activated memory cells in the myelinreactive pool in MS patients (18,19). Here, we provide definitive evidence that Kv1.3 ϩ is highly expressed in the perivenular and parenchymal inflammatory infiltrates of MS brain tissue and on T cells from the cerebrospinal fluid (CSF).…”
Section: Ultiple Sclerosis (Ms) Is An Immune-mediated Disorder Insupporting
confidence: 92%
“…In contrast, myelin-reactive T cells from the PB of healthy controls are Kv1.3 low , consistent with a naive͞T CM phenotype (11). Our results corroborate reports by other investigators who have found a preponderance of chronically activated memory cells in the myelinreactive pool in MS patients (18,19). Here, we provide definitive evidence that Kv1.3 ϩ is highly expressed in the perivenular and parenchymal inflammatory infiltrates of MS brain tissue and on T cells from the cerebrospinal fluid (CSF).…”
Section: Ultiple Sclerosis (Ms) Is An Immune-mediated Disorder Insupporting
confidence: 92%
“…The CT60 allele may affect the memory T cell subset because these cells may be subject to greater regulation by CTLA-4 (30) and thus potentially their isoforms. Moreover, although autoreactive T cells are present in healthy subjects and those with autoimmune disease, those circulating in individuals with autoimmune disease are in an activated/memory state (31)(32)(33). However, it is tempting to speculate that the CT60 allelic variant in the CTLA4 region lowers the threshold of activation by naive, CD4 ϩ CD45RA high T cells, allowing self-antigen reactive T cells to enter into an activated state directly leading to autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that in patients with MS, myelin basic protein reactive T cells are less dependent on CD28 co-stimulation indicating a different state of activation of potentially pathogenic T cells. 101 The dependency on CD28 co-stimulation is also related to the strength of the signal delivered to the cells. T-cell activation induced by weak agonists or antigens provided at low concentration is dependent on co-stimulation.…”
Section: Co-stimulation Dependence Of Naïve and Memory T Cellsmentioning
confidence: 99%
“…The different requirement for B7 co-stimulation suggests that memory cells that are chronically exposed to CNS auto-antigens are in a different state of activation compared to cells from healthy individuals. 101 A phase I, dose-escalation study to evaluate the safety and tolerability of CTLA-4Ig in patients with relapsingremitting MS was completed at the Partners Multiple Sclerosis Center (Boston, MA). We evaluated the disease-specific safety of a single infusion of CTLA-4 Ig in patients with relapsing-remitting MS, as well as the effects on immune functions of these patients.…”
Section: Co-stimulatory Blockade Treatments In Human Autoimmune Diseasesmentioning
confidence: 99%